Morphological Variation of “Jamur So” (Scleroderma sp.) from Purworejo Regency, Central Java - Pratiwi, Ambar; Putri, Diah Asta; Gultom, Putri Syifa; Indah, Rosiana; Sasongko, Hadi (Journal of Biotechnology and Natural Science, 2022)
Fungal diversity is high in Indonesia, one of which is Scleroderma sp. Scleroderma forms a symbiotic relationship with Gnetum gnemon. Its fruiting body is puff-ball shaped, and its gleba can be consumed because of its taste and nutritious. Study on the Scleroderma’s diversity in Purworejo Regency has not been done. In this study, morphological characteristics were used as main identification character. Scleroderma samples were collected from Grabag, Kemiri, and Kaligesing and then observed their morphology and spore characteristics. Morphological traits observed on fruit body shape (globose and kidney-shaped); and ornamentation on peridium layer (cracked, nodule and peeling). Chemical content, temperature, and humidity of the soil were also observed as supporting data.